PENANGANAN PRAKTIK PENCURIAN IKAN ILLEGAL DI PERAIRAN INDONESIA - Matompo, Osgar S (Faculty of Law, University of Muhammadiyah Malang, 2018)
Indonesia became one of the country's fisheries resources that have a very large in the world. But the fisheries potential of the above can be used optimally by the nation of Indonesia, due to rampant illegal fishing practices occurred (illegal fishing) committed by a foreign-fishing that fishing in indonesia. Do not handled the problem of illegal fishing professionally by the Government makes the problem becomes complex and complicated so this condition is exploited by the fisheries from another country to do activities that violating the provisions of the legislation.